Hyponatremia as a risk factor for pressure ulcers in patients treated in palliative care ward – preliminary reports - Sternal, Danuta; Szewieczek, Jan (Medycyna Paliatywna/Palliative Medicine, 2016)
Introduction: Assessment of risk factors for developing pressure ulcers is a part of palliative care. In the literature, there are few reports on the possible significance of hyponatremia in the development of pressure ulcers. Material and methods : Observational study was performed in 100 consecutive patients aged 71.1 ±11.9 years (± SD), including 57% women and 43% men, hospitalized in the Department of Palliative Care. 95% were oncology patients. Patients were divided into following groups: A (without pressure ulcers), B (admitted with pressure ulcers) and C (at which pressure ulcers developed during hospitalization). Among patients with pressure ulcers the following groups were specified: T (pressure ulcers have healed) and N (pressure ulcers have not healed). The Waterlow pressure ulcer risk assessment scale was used. On admission and during hospitalization (depending on the clinical indications) concentration of sodium in serum was measured. Results: In group C, the tendency to hyponatremia was higher than in group A (128.8 ±7.0 vs. 134 ±5.9 mmol/l; p = 0.018). Similarly, in group N the tendency to hyponatremia was higher than in group T (117.1 ±6.8 vs. 135.6 ±2.6 mmol/l, p = 0.018). Conclusion : Hyponatremia is a possible risk factor for the development and impaired healing of pressure ulcers. Confirmation of these findings requires further study.